Back Cover: Fe0 Nanomotors in Ton Quantities (1020 Units) for Environmental Remediation (Chem. Eur. J. 14/2016). Issue 14 (5th February 2016) - Teo, Wei Zhe; Zboril, Radek; Medrik, Ivo; Pumera, Martin
Abstract : Bubble‐propelled Fe 0 Janus nanomotors show their potential as decontamination agents of pollutants in Indonesian coral reefs. Enhanced pollutant decomposition triggered by biocompatible Fe 0 motors, which can be handled in air and fabricated in ton quantities for a low cost, will revolutionize the way the environmental remediation is carried out. More information can be found in the Full Paper by M. Pumera et al. on page 4789 ff.